The behaviour of adult Sitona lepidus Gyllenhal (Coleoptera Curculionidae) in response to white clover - Hardwick, S.; Harens, B. (New Zealand Plant Protection, 2000)
Individual adult Sitona lepidus were given the choice between damaged or undamaged seedlings mature plants of white clover damp soil or a blank in laboratory experiments carried out in a simple olfactometer Adult weevils displayed five different behavioural responses two of which head lifting and antennal movement appeared to be associated with host location In choice tests 7484 of adults chose a white clover plant over the blank or damp soil When given a choice 72 of adults selected white clover seedlings over mature plants Root and leaf damage did not affect response of S lepidus to white clover seedlings